PENGARUH PENDEKATAN-PENDEKATAN KONFLIK TERHADAP PENGEFEKTIFAN MANAJEMEN PADA KOPERASI TAKSI DI JAKARTA - Yolanda Masnita Siagian (Media Riset Bisnis & Manajemen, 2004)
Conflict can be a stimulating part of life and an energizer in the workplace. Property ad- dressed, we can make it work for us - and keep ourselves out of court. Although conflict management is of crucial importance in organizations, there is considerable confusion about the true nature of confict In this paper amodel which clearly identifies the key factors which contribute to organizational conflict. Anew contingency model that can be used by managers to select the most appropriate confictmanagement style depending on the circumstances of the particular conflict situation. This study also showed that the higher up the organizational hierarchy you move, the more time you will be likely to spend in conflict management.